2019
DOI: 10.3390/polym11121963
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolysis of Poly(lactic acid) as a Way to Extend the “Life Cycle” of This Material

Abstract: The article concerns the use of glycerolysis reaction as an alternative method of processing post-production and post-consumer waste from poly(lactic acid) (PLA). Management of waste is a very important issue from an environmental protection and economic point of view. Extending the “life cycle” of PLA is extremely important because it allows to make the most of this material. It also limits economic losses resulting from its disposal in the biodegradation process at the same time. This paper presents a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Borowicz et al carried out glycerolysis of waste poly(lactic acid) in order to obtain oligomeric polyhydric alcohols. Authors concluded that the chemical structure and other physicochemical properties of the final polyols indicated that they could be an alternative to petrochemical polyols [ 14 ]. Modification of lignin, a by-product in the pulp and paper industry, has also been described in several studies concerning the synthesis of polyols and their use in polyurethane formulations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Borowicz et al carried out glycerolysis of waste poly(lactic acid) in order to obtain oligomeric polyhydric alcohols. Authors concluded that the chemical structure and other physicochemical properties of the final polyols indicated that they could be an alternative to petrochemical polyols [ 14 ]. Modification of lignin, a by-product in the pulp and paper industry, has also been described in several studies concerning the synthesis of polyols and their use in polyurethane formulations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the HN of eco-polyol resulted mainly from the use of an equal amount of ethylene glycol in relation to the PLA waste. A large amount of the glycolyzing agent led to obtaining more shorter chains of lactic acid oligomer, while increasing HN of this product [ 6 ]. The acid numbers (AN) of the obtained polyols were 4.2 mg KOH/g for MSA-based polyol and 2 mg KOH g for PLA-based polyol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The largest source of polyol raw materials are products derived from processing of crude oil. Current research and technology trends aim to replace them with raw materials of natural origin [ 4 ] or with raw materials obtained as a result of recycling (extending the “life cycle”) [ 5 , 6 , 7 ]. Such research is carried out in two aspects: replacing components from non-renewable sources with their renewable counterparts and reducing the emission of non-degradable waste into the environment as a result of introducing components that favor their biodegradation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study performed alcholysis using metal compounds and ionic liquids [ 16 , 17 ]. Disintegration of PLA using organometallic compounds has also been investigated [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, these approaches are not suitable for compositing because of the use of chemical compounds, which add to the environmental load.…”
Section: Introductionmentioning
confidence: 99%